ECOLOGICAL ASPECTS OF CARROT TRAIT VARIATION - T. V. Khmelinskaya; V. I. Burenin; E. V. Pryanishnikova (Овощи России, 2017)
Recently, the particularities in carrot trait variation, namely root color and shape; carotene content; duration of vegetative period; resistance to diseases and pests have been established. But such traits as yield capacity, root marketability, root quality, long-storability as well as their genetic  determination haven’t  been  well  studied. Consequently, thorough study of  genetically diverse accessions and the search for phenotypically well-identified traits are very actual tasks. The ecological and geographical study of carrot enables to reveal polymorphisms among cultivars, in order to use it in the breeding program. The study of collection accessions of local and foreign origin in contrasted conditions varying in temperature and water regimes revealed the significant variation of main biological and economically valuable traits, including root yield and quality. The root yield was substantially higher in Pushkin (Leningrad oblast) than in Vologda oblast. Comparatively stable yield and quality were shown in local cultivars:   ‘Nanatskay  Krasnaya’,  ‘Princess’   and ‘Gribovskaya’. Very important requirement for highly marketable products is the cultivar resistance to disease and pests. There are no completely resistant genotypes to carrot psylla among accessions studied. Carrot accessions bearing resistance to the pest and also showing high productivity and quality were ‘Losinoostrovskaya 13’ (Russia), ‘Gavrilovskaya’ (Ukraine), ‘Feonia’ (Denmark), ‘New Model’ (UK), ‘Betina’ (the Netherlands) that can be used for breeding program. ‘Krasnaya Dlinnaya’ (Russia) and ‘Chantenay а Coeur Rouge’ (France) were comparatively  resistant to powdery mildew.